De arregaçar as mangas: idiomatic expressions and proverbs in teaching brazilian portuguese to hispanic speakers from a contrast perspective - OLIVEIRA, GABRIEL AMANCIO DE OLIVEIRA; Ferreira, Cláudia Cristina (The ESPecialist, 2024)
Language teaching allows teachers to give students the chance to occupy spaces in different spheres. Some learn a language for personal tastes, others for professional reasons. When we learn another language, in addition to the linguistic aspects, we get to know cultural nuances and the way a society conceives the world based on its experiences and formulates its vision according to social identification. Therefore, the aim of this paper is to present and discuss the use of idiomatic expressions for teaching Portuguese to Spanish speakers, as well as contrasting them with expressions in the Spanish language. We believe that phraseology, which is the combination of words with a degree of idiomaticity, contributes to the communication of interlocutors (CORPAS-PASTOR, 1996; ZULUAGA, 2003; XATARA, 2013; ORTIZ ALVAREZ, 2014; MONTEIRO-PLANTIN, 2014). In this way, we show Brazilian Portuguese expressions that are used in everyday communication and that can be used in teaching Portuguese to natural Spanish speakers. Making use of phraseological elements in foreign/additional language classes can be a challenge for teachers who are already accustomed to the way they are taught. However, we would like to point out that teaching Portuguese as a mother tongue (PLM) is different from teaching it as a foreign/additional language (PLE), and seeking training is necessary in order to incorporate elements that are widespread in the culture and language in which the learners are inserted, since they contribute to their mastery of the language. In this way, we conclude that using idiomatic phraseology in the classroom is a support for teachers, since language and culture are inseparable, and presenting elements such as jargon, slang, proverbs, among others, enriches language learning.